2003
DOI: 10.1021/jp036859v
|View full text |Cite
|
Sign up to set email alerts
|

Molten and Solid Trialkylsulfonium Iodides and Their Polyiodides as Electrolytes in Dye-Sensitized Nanocrystalline Solar Cells

Abstract: Potential new electrolytes for dye-sensitized nanocrystalline solar cells (DNSCs) of Gra ¨tzel type based on trialkylsulfonium iodides have been investigated. Room temperature molten salts of (Et 2 MeS)I, (Bu 2 MeS)I, and (Bu 2 EtS)I, with iodine in low concentrations, revealed good conducting abilities. DNSCs using iodinedoped (Bu 2 MeS)I as electrolyte achieved an overall light-to-electricity conversion efficiency of 3.7% in simulated AM 1.5 solar light at a light intensity of 0.1 Sun. The effects from varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 25 publications
(54 reference statements)
0
50
0
1
Order By: Relevance
“…Other ILs with cations such as sulfonium, [43] guanidinium, [44] ammonium, [45] or phosphonium [46] have also been explored as solvent-free electrolytes; however, they show low device efficiencies due to high viscosity and mass transport limitations of the photocurrent under full sunlight. At room temperature, the IL dibutylmethylsulphonium iodide with low concentration of iodine achieved an overall light-toelectricity conversion efficiency of 3.7% under a simulated AM 1.5G and 0.1 sunlight intensity.…”
Section: Non-imidazolium Cation-based Ionic Liquidsmentioning
confidence: 99%
“…Other ILs with cations such as sulfonium, [43] guanidinium, [44] ammonium, [45] or phosphonium [46] have also been explored as solvent-free electrolytes; however, they show low device efficiencies due to high viscosity and mass transport limitations of the photocurrent under full sunlight. At room temperature, the IL dibutylmethylsulphonium iodide with low concentration of iodine achieved an overall light-toelectricity conversion efficiency of 3.7% under a simulated AM 1.5G and 0.1 sunlight intensity.…”
Section: Non-imidazolium Cation-based Ionic Liquidsmentioning
confidence: 99%
“…[33] Hydrophobic trialkylsulfonium ILs based on perfluorinated anions were also reported, and their potential applications as promising electrolytes in lithium batteries and dye-sensitized solar cells were preliminarily investigated. [34] However, information on the synthesis of ILs based on a cyclic sulfonium cation is relatively limited in previous literature. [35] Therefore, there is still some room to develop new sulfonium-based ILs that may be liquids at lower temperatures, and it should be expected that these novel ILs would possess the characteristics of low viscosity and high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Paulsson et al [74] − /I − couple. However, the rareness of selenium and high costs has limited its application in DSC.…”
Section: Electrolytementioning
confidence: 99%
“…Grätzel et al reported the solar cells based on low-viscosity ionic liquid and MPII mixture. Figure 6 and Table 2 summarize the structure and viscosity of some ionic liquid and the photovoltaic performance of DSC based on ionic liquid electrolyte of different composition [73][74][75][76][77][78][79][80][81][82][83].…”
Section: Electrolytementioning
confidence: 99%